Study of Linguistic Relativity on The Dynamics Of Language Meaning between Entrepreneurial Mindset Concepts in Indonesian Culture - Rosalina, Erlyn; Sari Wulandari, Linda (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
Language is dynamic, one of which is the change in meaning that is strongly influenced by cultural development. The culture of a society depends on the development of science and technology that can affect people's mindsets from different generations. There are several generational groups, namely silent generation/matures (<1946), baby boomers (1947-1964), generation X (1965-1980), generation Y or millennials (1981-1995), and generation Z (1996-present). However, people who are still in their productive age are Generation X, Y, and Z. The purpose of the research is to describe the dynamics of the meaning of the entrepreneurial mindset in generations X, Y, and Z, as well as the relationship between the concept of entrepreneurial mindset and culture of Indonesian society. This research was conducted through linguistic relativity studies. The method used is a descriptive qualitative and quantitative method with data analysis using the triangulation technique. This research involved 57 respondents from generation x, y, and z groups. The data of this research is in the form of questionnaire results based on the mindset of entrepreneurs and the culture of Indonesian society. The result is there are four proverbs that are contrary to the mindset of the entrepreneur, that is, savings base rich and a little bit long to become a hill in contrast with the way of mindset do not save money. But there are four verses that are in line with the mindset of the entrepreneur, that is, a day is a thread, a year is a piece of cloth, and the first time is fun, then is pain, then it is fun. The mindset of the X, Y, and Z generations is more likely to use the mindset of Indonesian culture.